Regioselective and late-stage polyfluoroarylation of arenes with diverse fluoroaryl nucleophiles via Pd-catalysis. Issue 21 (8th September 2022) - Liang, Lei; Wang, Yue-Hui; Li, Chen; Wang, Hua-Jie; Yang, Qi-Liang; Li, Chang-Gong; Qu, Gui-Rong; Guo, Hai-Ming; Niu, Hong-Ying
Abstract : Dehydrogenative coupling of arenes with fluoroaryl nucleophiles enables the efficient synthesis of fluoroaromatic compounds from readily available starting materials. Abstract : Dehydrogenative coupling of arenes with fluoroaryl nucleophiles enables the efficient synthesis of fluoroaromatic compounds from readily available starting materials. Although considerable progress has been made in direct C(sp 2 )–H bond polyfluoroarylation, significant limitations in the regioselective functionalization of complex molecules and the scope of Ar F groups still exist. We report here a highly selective method to address these long-standing limitations via a tandem activation/cross-coupling strategy. This method tolerates a wide range of arenes, pharmaceutically relevant aromatic compounds and polyfluoroaryl nucleophiles.